WHY DO STUDENT TEACHERS NEED CULTURAL KNOWLEDGE? AN EXAMPLE FROM FIELD TEACHING PRACTICE - Tri Wahyuni Floriasti (ETERNAL (English Teaching Journal), 2012)
People especially teenagers tend to use language to represent their characters, for example they use slang and inappropriate words in the wrong situation. One attempt had been done to give young generation, especially English student teachers in Indonesia, English lesson, which was inserted with multicultural values. This effort was not only adding and applying universal values and cultural identities, which match with students’ needs, but also managing, and running good strategies in teaching learning process.  Why multicultural? Indonesia consists of 17.506 islands, 746 languages, and 1.128 tribes. It can be said that Indonesia is a multicultural country, which enriches the national heritage and strengthens the identity of Indonesians as well. However, the diversity itself may trigger potential conflict among Indonesian. Knowing, learning, comprehending and applying the knowledge of culture in daily life will glue them and avoid the future conflict. Therefore, giving multicultural knowledge to student teachers is one of the practical ways to enlighten them how to appreciate differences then go hand in hand with others in Indonesia and in the world. At the end, they will not only play as good model for their students but also occupy themselves as transformers of multicultural knowledge.